Does free or lower cost smoking cessation medication stimulate quitting? Findings from the International Tobacco Control (ITC) Netherlands and United Kingdom Surveys - F. A. Van den Brand; Gera E. Nagelhout; Karin Hummel; Marc C. Willemsen; Ann McNeill; C. P. Van Schayck (Tobacco Induced Diseases, 2018)
Background Free or lower cost cessation medication is reported more often as a trigger to think about quitting by smokers with low education and/or income, but it is not clear whether this leads to actual quitting of smoking. The aim of this study was to investigate whether reporting free medication as trigger is related to medication use, reported quit attempts and quit success and whether this association is modified by education and income.